Swedish slanguage : a fun visual guide to Swedish terms and phrases - Ellis, Mike, 1961- (Slanguage, 2017)
Swedish Slanguage provides translations and pronunciation guides for approximately 300 English words and phrases. Use the pronunciation guide to say them out loud a few times, and soon you'll be speaking basic Swedish words and phrases like "How are you?" (Hear More Due?) and "Cold" (Fur Shilling).